2020
DOI: 10.1016/j.fuproc.2019.106271
|View full text |Cite
|
Sign up to set email alerts
|

Tar conversion of biomass syngas in a downstream char bed

Abstract: The catalytic conversion of biomass-derived tars over char during long tests (over 6 hours) is studied. The syngas is generated in a steam-blown fluidized-bed gasifier employing wood pellets and conducted to a second tubular reactor where non-activated char particles are fluidized. The gasifier operated at 750 °C whereas the temperature of the secondary reactor was varied between 750 °C and 875 °C. The evolution of the tar conversion, gas composition and internal structure of the used catalysts were studied. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 34 publications
3
6
0
Order By: Relevance
“…For samples with C > 1000, the surface area of the micropores contributes over 85% to the overall surface area, with a strong correlation between the C parameter value and the micropore ratio for SSA (R 2 =0.833) as well as V pore (R 2 =0.780) (Figure 3; SI -Table S2, S3, S6). data [18,[54][55][56][57][58][59][60][61][62]).…”
Section: Pore Specific Model: Hs-nldftmentioning
confidence: 99%
See 3 more Smart Citations
“…For samples with C > 1000, the surface area of the micropores contributes over 85% to the overall surface area, with a strong correlation between the C parameter value and the micropore ratio for SSA (R 2 =0.833) as well as V pore (R 2 =0.780) (Figure 3; SI -Table S2, S3, S6). data [18,[54][55][56][57][58][59][60][61][62]).…”
Section: Pore Specific Model: Hs-nldftmentioning
confidence: 99%
“…swelling, during interaction with the adsorptive [33]. Braida et al [62] showed that biochars are nonrigid-structured adsorbents during the sorption of benzene and the ability of biochar to swell was further indicated in studies on PAH extraction using organic solvents as well as during H 2 O vapour adsorption measurements [71][72][73][74].…”
Section: Open Hysteresis and Adsorption Induced Pore Deformationmentioning
confidence: 99%
See 2 more Smart Citations
“…They reported the effects of the amount and composition of tar and temperature on the tar-reforming reaction. Fuentes-Cano et al reported the model tar decomposition over biomass char in gasification conditions. They reported not only the experimental proof of char reactivity for tar model compounds but also a kinetic model.…”
Section: Introductionmentioning
confidence: 99%